A Task Scheduling Strategy for Utility Maximization in a Renewable-Powered IoT Node; IEEE Global Communications Conference (GLOBECOM 2018) - Leithon J. Johann; Suarez L. A. Luis; Dzhayakodi Arachshiladzh D. N. K. Dushanta Nalin Kumara; Anis Muhammad M. Moiz (2018, 2018)
Title screen